Análisis de la imagen corporativa de la Diócesis de Latacunga - Caiza López, Joselyn Ibeth (2023)
The objective of this research work is to analyze the corporate image of the Diocese of Latacunga to determine whether the people who interact whit if feel identified with the institutional mission and vision. It is essential to point out that this topic is currently relevant in the organizational and business world; therefore, this project aims to analyze the impact of the activities carried out and how they affect the corporate image. Employing the support of theoretical bases of different authors and with the use of the methodological framework, the quantitative approach was used, a non-experimental design, a descriptive level, the techniques of the survey and direct observation were applied, the questionnaire and the observation sheet were used as instruments focused on the collection of data to be able to analyze the activities carried out, visual elements that they possess and channels of communication that the diocese manages before its parishioners. Through the results obtained, it was observed that currently, the Diocese if Latacunga does not have visual elements that help to identify itself quickly and to recognize what principles it works with (Mission and Vision), also that the Corporate Image of the Diocese of Latacunga is being affected by the lack of visual elements and images as there do not transmit and religious message. Therefore, to solve the existing problem, we propose the modification of the logo, the use of a panel where the mission and vision of the diocese are visibly placed, the creation of an official page on the social network Facebook and the incorporation of a digital Brochure.